2022
DOI: 10.1108/bjm-01-2021-0027
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management strategies and organizational improvisation: what changed after the emergence of technological turbulence caused by artificial intelligence?

Abstract: PurposeThis paper aims to analyze the moderating effect of technological turbulence caused by artificial intelligence on the relationship between the traditional knowledge management strategies of personalization (tacit knowledge) and codification (explicit knowledge), and organizational improvisation, which refers to the firm's ability to generate ideas and respond to changes in the technological environment in real time. Until now, individuals have played a key and indispensable role in organizational improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 62 publications
(232 reference statements)
0
9
0
2
Order By: Relevance
“…We suspect that employees' opportunistic behaviors could diminish the positive impact of CO and BAC on agility. Beyond the fact that our results have demonstrated that external pressures for artificial intelligence adoption do not represent a technical problem for the company, we are fully convinced that employees are resorting to a variety of strategies to protect their personal interests at work when facing the imminent risk of being replaced by artificial intelligence applications (Arias-P erez and Cepeda-Cardona, 2022;Truong and Papagiannidis, 2022).…”
Section: Theoretical and Practical Contributionsmentioning
confidence: 70%
See 2 more Smart Citations
“…We suspect that employees' opportunistic behaviors could diminish the positive impact of CO and BAC on agility. Beyond the fact that our results have demonstrated that external pressures for artificial intelligence adoption do not represent a technical problem for the company, we are fully convinced that employees are resorting to a variety of strategies to protect their personal interests at work when facing the imminent risk of being replaced by artificial intelligence applications (Arias-P erez and Cepeda-Cardona, 2022;Truong and Papagiannidis, 2022).…”
Section: Theoretical and Practical Contributionsmentioning
confidence: 70%
“…On the contrary, this positive moderating effect may indicate that this type of external pressure can be viewed as an opportunity for the company to adopt the best and most advanced digital transformation practices in the industry (Ashrafi et al ., 2019; Bag et al ., 2021). Even the fact that external pressures to adopt artificial intelligence are only positive and significant in the second stage of the mediation (BAC → OA) indicates that when the firm has reached a certain degree of digital maturity, it has enough technical and relational knowledge to easily resolve any incompatibility between its internal digital resource base and any external technological standard (Arias-Pérez and Cepeda-Cardona, 2022). However, the most interesting aspect of this finding is that once the company has reached that stage of maturity, it can understand the complexity of this type of external pressure and even find new ways of maximizing the use of artificial intelligence to improve OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, employee improvisation helps organizations cope with dynamic and complex external environments. 60 This research found that empowering leadership activates employee improvisation, encouraging organizational managers to adopt this leadership style, which is beneficial with respect to improve organizational flexibility and obtaining a competitive advantage. In daily work, leaders are encouraged to provide employees with job autonomy, actively transfer information related to work meaning, and trust employees to achieve high performance.…”
Section: Practical Implicationsmentioning
confidence: 87%
“…KM provides long-term advantages for organizations and societies and their utilization of human, intellectual and informational capital (Di Vaio et al, 2021). As new financial technologies become an integral part of banking and banks begin to compete beyond financial services in the face of increasing competition from nonbanking institutions, traditional banks lost part of their market share as a result (Arias-Pérez & Cepeda-Cardona, 2022). Moreover, the main issue that banks are facing is encouraging and increasing the compliance of bank customers to apply financial technologies to facilitate and speed up banking activities and increase efficiency by increasing transparency and reducing the perceived risk of customers.…”
Section: The Mediating Role Of New Financial Technologiesmentioning
confidence: 99%